2016
DOI: 10.1007/s10681-016-1717-z
|View full text |Cite|
|
Sign up to set email alerts
|

Seed dormancy QTL identification across a Sorghum bicolor segregating population

Abstract: Pre-harvest sprouting (PHS) in Sorghum bicolor is one of the main constrains for its production in the central region of Argentina, as grain maturation often coincides with rainy or high environmental humidity conditions. The obtention of more dormant genotypes with higher PHS resistance has always been a desirable trait for breeders but the typical quantitative nature of seed dormancy makes its manipulation difficult through classical breeding. Dissecting this quantitative variability into quantitative trait … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…One hundred and sixty-nine sorghum target genes initially identified for multi-stress tolerance were found to be associated with QTLs responsible for various traits. This includes 37 (21.9%) genes associated with drought adaption [ 47 ], 84 (49.7%) genes responsible for grain yield, flowering time, and stay-green traits [ 48 ] and 28.4% of the genes associated with seed dormancy [ 49 ] ( Table 3 ; S16 Table ). This study also identified 21 target genes in maize that are associated with drought QTLs of different agronomic purposes using sequence alignments based on Gramene QTL release [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One hundred and sixty-nine sorghum target genes initially identified for multi-stress tolerance were found to be associated with QTLs responsible for various traits. This includes 37 (21.9%) genes associated with drought adaption [ 47 ], 84 (49.7%) genes responsible for grain yield, flowering time, and stay-green traits [ 48 ] and 28.4% of the genes associated with seed dormancy [ 49 ] ( Table 3 ; S16 Table ). This study also identified 21 target genes in maize that are associated with drought QTLs of different agronomic purposes using sequence alignments based on Gramene QTL release [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…In order to evaluate if some of the genes identified in this study for sorghum multi-stress responses are co-localized within any of the QTLs previously identified for stress tolerance, we examined and compared the genomic coordinates of the target genes with the QTLs known for drought tolerance [ 47 49 ]. The target genes that fall within the QTLs genomic regions were considered as potential candidates for association with these QTLs.…”
Section: Methodsmentioning
confidence: 99%
“…In order to identify target DRGs that were associated with different QTLs, we first obtained the genomic location of the QTLs based on the previous studies [ 33 , 80 , 81 ] and compared with the genomic position of the genes currently identified. If the gene coordinates overlap with or fall in the QTLs regions, then we considered that there was high chance that the genes were associated with the QTLs as they were co-localized.…”
Section: Methodsmentioning
confidence: 99%
“…These authors used RFLP, RAPDs, and AFLP markers, and reported a putative association between SbVP1 and a dormancy QTL in likage group “E” ( Carrari et al, 2003 ). To further confirm and expand these results, a new mapping population was obtained from the same sorghum parents, the genetic map was constructed using SSR markers, and phenotypic data were obtained at 34 (before PM) and 45 (after PM) DAP ( Cantoro et al, 2016 ). In this work, six QTLs were identified for seed dormancy ( Figure 2 ) in 42 DAP grains (qGI-1, qGI-3, qGI-4, qGI-6, qGI-7, and qGI-9) which were successfully anchored on the S. bicolor genome assembly v2.1 ( Paterson et al, 2009 ) through QTL flanking SSR physical position.…”
Section: Genetic Approach: Mapping Of “Old” Candidate and “New” Dormamentioning
confidence: 99%
“…A biological role for these interactions in the expression of dormancy of sorghum grains was proposed: either SbABI4 and/or SbABI5 activate transcription of the SbGA2-oxidase3 gene in vivo and promote SbGA2-oxidase3 protein accumulation; this would result in active degradation of GA 4 , thus preventing germination of dormant grains. A comparative analysis of the 5′ -regulatory region of GA2-oxidase genes from both monocots and dicots showed that GA2-oxidase genes with an ABRC in their promoter region are exclusive to a conserved sub-group found in monocots (sub-group M3, according to Cantoro et al, 2016 ) to which SbGA2-ox3 belongs. Conservation of the ABRC in closely related GA2-oxidases from Brachypodium distachyon and rice suggests that these species might share the same regulatory mechanism as proposed for grain sorghum.…”
Section: Expression Of Several Aba Signaling Genes and A Ga Catabolismentioning
confidence: 99%